O adolescente em conflito com a lei : representações sociais e julgamentos de estudantes de direito - Costa, Luiza Lins Araujo (2016)
The aim of this research was to explore the impact of skin color and social strata of adolescents in conflict with the law on social representations and judgments of law students. In this study, 102 students participated, between the fifth and the tenth period of law, within a private college located in Aracaju-SE. The ages ranged between 20 and 62 years (M = 27.9, SD = 8.06), 54 male participants (52.9%). The study was conducted with an experimental design. On the instrument, we presented a case of an infractional act and manipulated among the groups the variables skin color and social stratum of the adolescent. After reading the case, participants were asked which of the socioeducational measures provided by the Child and Adolescent Statute (ECA) would be applied to the juvenile offender. The instrument also contained items about the social representation of the adolescent in conflict with the law, attitude towards the reduction of the criminal responsibility age, explanations for the infractional conduct and representations of the future of adolescents in conflict with the law. The results indicate that imprisonment, most severe penalty, is the most applied by participants (44.1%). Contrary to what predicted our hypothesis, there were no significant statistical differences in the application of the measures based on skin color and social strata of the adolescent and there was also no effect of these variables on social representations. However, we identified a representation objectified by contextual elements as "Problems in education" and "poverty", besides of pejorative (marginal, vagabond) and essentialist (offender, criminal) terms indicating a view of criminal behavior as definitive condition for these adolescents. Based on the literature and in the light of the results we discussed relations between social representations, prejudices and judgments within the Justice for Children and Youth in Brazil.